Mortality trends in pulmonary arterial hypertension in Canada: a temporal analysis of survival per ESC/ERS guideline era. Issue 6 (2nd June 2022) - Zelt, Jason G.E.; Sugarman, Jordan; Weatherald, Jason; Partridge, Arun C.R.; Liang, Jiaming (Calvin); Swiston, John; Brunner, Nathan; Chandy, George; Stewart, Duncan J.; Contreras-Dominguez, Vladimir; Thakrar, Mitesh; Helmersen, Doug; et al.
Background: The evolution in pulmonary arterial hypertension (PAH) management has been summarised in three iterations of the European Society of Cardiology/European Respiratory Society (ESC/ERS) guidelines. No study has assessed whether changes in management, as reflected in the changing guidelines, has translated to improved long-term survival in PAH. Methods: We performed a mixed retrospective/prospective analysis of treatment-naïve, incident PAH patients (n=392) diagnosed at three major centres in Canada from 2009 to 2021. Patients were divided into two groups based on their diagnosis date and in accordance with the 2009 and 2015 ESC/ERS guideline iterations. Overall survival was assessed based on date of diagnosis and initial treatment strategy ( i.e. monotherapy versus combination therapy). Results: There was a shift towards more aggressive upfront management with combination therapy in Canada after the publication of the 2015 ESC/ERS guidelines (10.4% and 30.8% in patients from 2009 to 2015 and 36.0% and 57.4% in patients diagnosed after 2015 for baseline and 2-year follow-up, respectively). A key factor associated with combination therapy after 2015 was higher pulmonary vascular resistance (p=0.009). The 1-, 3- and 5-year survival rates in Canada were 89.2%, 75.6% and 56.0%, respectively. Despite changes in management, there was no improvement in long-term survival before and after publication of the 2015 ESC/ERS guidelines (p=0.53). Conclusions: There was an increase in the use of initial and sequential combination therapy in Canada after publication of the 2015 ESC/ERS guidelines, which was not associated with improved long-term survival. These data highlight the continued difficulties of managing this aggressive pulmonary disease in an era without a cure. Incident PAH patients in Canada have been treated more aggressively in recent years, reflecting changing ESC/ERS guideline recommendations, but this was not mirrored by incremental improvement in survival since 2015 https://bit.ly/3lyc1Oc